Odpowiedzi

2010-02-09T19:25:47+01:00
3x+2y=2
5x+4y=6

2y = 2 - 3x
5x + 2(2 - 3x) = 6
(bo 4y = 2*2y czyli 2*(2 - 3x))

5x + 4 - 6x = 6
-x = 6 -4
-x = -2 |*(-1)
x = 2

2y = 2 - 3x
2y = 2 - 3*2
2y = 2 - 6
2y = -4 |:2
y = -2
1 5 1
Najlepsza Odpowiedź!
2010-02-09T19:30:18+01:00
3x+2y=2
5x+4y=6

2y=2-3x /:2
5x+4y=6

y=1-1,5x
5x+4y=6

y=1-1,5x
5x+4*(1-1,5x)=6

y=1-1,5x
5x+4-6x=6

y=1-1,5x
-x=2 /: (-1)

y=1-1,5x
x=-2

y=1- 1,5* (-2)
x=-2

y= 1+3
x=-2

y=4
x=-2

;]]
2010-02-09T19:33:49+01:00
3x+2y=2
5xy=2
xy=2podzielic na 5
xy=0,4


5x+4y=6
9xy=6
xy=0,6